Impact of IVF/ICSI on grades of placenta accreta spectrum disorders and pregnancy outcomes - Miao Hu; Lili Du; Lizi Zhang; Lin Lin; Yuliang Zhang; Shifeng Gu; Zhongjia Gu; JingYing Liang; Siying Lai; Yu Liu; Minshan Huang; Yuanyuan Huang; et al. (Reproductive Health)
Abstract Objective IVF/ICSI is associated with an increased risk of placenta accreta spectrum disorders (PAS). Invasive PAS can result in significant adverse maternal and fetal outcomes. This study investigates the impact of IVF/ICSI on the severity grading of PAS and its correlation with pregnancy complications. Methods Placenta accreta spectrum disorders (PAS) patients who underwent cesarean section at a single clinical center from January 2018 to March 2023 were retrospectively included in this study. Baseline characteristics and outcomes were compared between the IVF/ICSI group (154 cases) and the spontaneous conception group (820 cases). Binary logistic regression was used to explore the risk factors associated with adverse outcomes related to IVF/ICSI. A 1:1 ratio propensity score matching (PSM) was conducted to minimize selection bias between the two groups (123 cases per group). Data analysis was performed using SPSS (version 25.0) software. Results PAS grading is not associated with IVF/ICSI (OR = 0.76, 95%CI: 0.45 ~ 1.27, P = 0.290). In contrast, a significant risk factor for postpartum hemorrhage (OR = 9.20, 95%CI: 2.68 ~ 9.22, P < 0.001) and red cells transfusion ≥ 4U (OR = 3.71,95%CI:1.21 ~ 11.33, P = 0.021) was observed in IVF/ICSI group. No additional adverse pregnancy outcomes arose as a result of IVF/ICSI. Conclusion IVF/ICSI does not increase the depth of placental implantation in patients with placenta accreta spectrum (PAS); however, it is associated with a higher risk of postpartum hemorrhage and the need for blood transfusion. In clinical practice, special attention should be given to the prenatal management of these patients, along with ensuring adequate blood product reserves during delivery.